Continuity and rupture in the long Middle Ages : religion, law and interpretation - Moore, Michael Edward (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"The "Long Middle Ages" indicates a span of time extending from Antiquity, across the Middle Ages, to the Early Modern period. The author tries to understand factors of historical continuity binding this period together, and the periodic scenes of violent change which disrupted societies and traditions. The Long Middle Ages were established on classical and biblical foundations, while each generation interpreted and expanded on those origins. The cohesion of the Long Middle Ages was brought about by continuous acts of reflection and renascence. Scholarly practices and ideas of Antiquity were taken up in the monasteries and cathedral schools of the Middle Ages, while during the Renaissance, and then the Baroque period, thinkers looked back to Antiquity and to the Middle Ages. Continuity and Rupture in the Long Middle Ages is an interdisciplinary approach to intellectual history, which puts the history of ideas in the context of cultural, political, religious and legal history. Medieval history is the central moment, while continuity and change are found in traditions extending from the Lord's Prayer (AD 30) to Jean Mabillon (AD 1632-1707), and onward to moderns like Ernst Cassirer and Paul Ricoeur. Readers will discover new significance in historical figures like the Venerable Bede, Boniface of Mainz, Charlemagne, and Pope Formosus - in the laws of medieval kings and bishops - and institutions like the Monastery of Cluny. These essays offer powerful new interpretations for students and researchers in the fields of medieval studies, legal and literary interpretation, legal history, and the history of European intellectual life from ancient to modern times"--
Demons and the battle for souls at Cluny -- Bede's devotion to Rome : the periphery defining the center -- The Frankish church and missionary war in Central Europe -- The attack on Pope Formosus : papal history in an age of resentment -- The body of Pope Formosus -- Carolingian monarchy and ancient Irish models of kingship -- The ancient fathers : Christian antiquity, patristics and Frankish canon law -- Canon law and royal power in the councils and letters of St. Boniface -- Philology and presence -- Our father : glossing a Bohemian prayer -- The god of culture -- Jean Mabillon and the sources of medieval ecclesiastical history (part 1) -- Jean Mabillon and the sources of medieval ecclesiastical history (part 2).
Keywords: Church history -- Middle Ages, 600-1500.; Church history -- Middle Ages, 600-1500 -- Historiography; Canon law -- History; Kings and rulers, Medieval; Middle Ages; Europe -- History -- 476-1492.; HISTORY / Medieval; HISTORY / Europe / Western